Intellectualization of air staff diagnostic database as means of improving professional readiness quality - Корсунов, Анатолий Рувимович (Technology audit and production reserves, 2014)
The problem of forming a diagnostic database for air staff by using modern facilities with intellectualizing capabilities is considered in the paper. Herewith, the development of such databases is provided with the necessary algorithms and modeling methods. The formation of a physiological database in a digital format with the automatic control implementation is proposed. In this regard, intellectualization concerns the database structure formation, as well as its technical input, which maintains the decision-making about a deviation level of body physiological parameters from specified ones for allowance of carrying out a flight assignment. Multilateral expert systems of evaluating medical data using a system, estimating the dynamics of diagnostics parameter changes are considered in the paper. It allows obtaining not only the dynamics of body changes, but also identifying general outlines of the most profound changes in it for running dіagnostics. Practical recommendations for applying the developed method by using modern means of communication have been worked out.